Biomechanical investigation of thoracolumbar spine in different postures during ejection using a combined finite element and multi‐body approach. (14th May 2014) - Du, Chengfei; Mo, Zhongjun; Tian, Shan; Wang, Lizhen; Fan, Jie; Liu, Songyang; Fan, Yubo
SUMMARY The aim of this study is to investigate the dynamic response of a multi‐segment model of the thoracolumbar spine and determine how the sitting posture affects the response under the impact of ejection. A nonlinear finite element model of the thoracolumbar‐pelvis complex (T9–S1) was developed and validated. A multi‐body dynamic model of a pilot was also constructed so an ejection seat restraint system could be incorporated into the finite element model. The distribution of trunk mass on each vertebra was also considered in the model. Dynamics analysis showed that ejection impact induced obvious axial compression and anterior flexion of the spine, which may contribute to spinal injuries. Compared with a normal posture, the relaxed posture led to an increase in stress on the cortical wall, endplate, and intradiscal pressure of 43%, 10%, 13%, respectively, and accordingly increased the risk of inducing spinal injuries. Copyright © 2014 John Wiley & Sons, Ltd.